Kidney simulation in 3 dimensional environment "digikid" / Dennis Foong Yew Han - Dennis Foong , Yew Han (2004)
DigiKid is a standalone system that promises quick and efficient way to gain knowledge on kidney anatomy. The entire learning experience is integrated with interactive 3D elements. DigiKid is available will cater the hunger for any individuals especially the non-biology students.The objectives of DigiKid are to create an interactive learning process in virtual reality environment. The user interface design is target at non- expert computer users to widen the scope of users. Rapid Application Development model is used to develop DigiKid . The tools involved in the development of DigiKid arc els MAX, Adobe Photoshop 7.0, Adobe Premiere Pro, Macromedia Director MX and much more. lt is hope that DigiKid will offer more know led re and information as well as promote the importance of kidney health lo the public. Getting to know kidney problems and diseases will make us aware of the damage done to our body at every second of our life. Quizzes and questions also enable users to determine the level of knowledge gain from the system. Repetitions of studies can be done if there appears to be any dissatisfaction of quiz results. Alter all, conducting a learning process offers more benefits than a one way traffic style or education absorption. This is why Digikid is created; interactive learning experience for all the eager learners out there. "Life is enjoyed when life is health "